1998
DOI: 10.1016/s0014-5793(98)01123-5
|View full text |Cite
|
Sign up to set email alerts
|

2D‐isolation of pure plasma and thylakoid membranes from the cyanobacterium Synechocystis sp. PCC 6803

Abstract: Aqueous polymer two-phase partitioning in combination with sucrose density centrifugation offered, for the first time, a 2D-separation method for the isolation of pure plasma and thylakoid membranes from the cyanobacterium Synechocystis 6803 without any cross-contaminations. The purity of the membrane fractions was verified by immunoblot analysis using antibodies against membrane-specific marker proteins. As an initiation of a proteomics project, two prominent proteins, which were observed only in the plasma m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
138
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(144 citation statements)
references
References 18 publications
4
138
1
Order By: Relevance
“…Unexpectedly, only a weak response was detected with Flv4 and Flv2 antibodies compared with that recorded in the total membrane fraction isolated by a standard method used in our laboratory (which includes high cation concentration; see Methods). However, no Sll0218 signal could be found in conventional two-phase fractions (Norling et al, 1998;Figure 2A).…”
Section: Cellular Location Of the Gene Products Of The Flv4-flv2 Operonmentioning
confidence: 99%
See 2 more Smart Citations
“…Unexpectedly, only a weak response was detected with Flv4 and Flv2 antibodies compared with that recorded in the total membrane fraction isolated by a standard method used in our laboratory (which includes high cation concentration; see Methods). However, no Sll0218 signal could be found in conventional two-phase fractions (Norling et al, 1998;Figure 2A).…”
Section: Cellular Location Of the Gene Products Of The Flv4-flv2 Operonmentioning
confidence: 99%
“…Although no transmembrane helices were predicted in any of the FDP sequences, we also found a strong association of the Flv2 and Flv4 proteins with the membrane fraction . To localize the Flv4, Sll0218, and Flv2 proteins precisely in the membrane fraction, the thylakoid and plasma membranes, purified by the two-phase partitioning method (Norling et al, 1998), were probed with protein specific antibodies. Unexpectedly, only a weak response was detected with Flv4 and Flv2 antibodies compared with that recorded in the total membrane fraction isolated by a standard method used in our laboratory (which includes high cation concentration; see Methods).…”
Section: Cellular Location Of the Gene Products Of The Flv4-flv2 Operonmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytoplasmic and thylakoid membranes were isolated by the 2D-separation method combined with sucrose density centrifugation (Norling et al, 1998;Huang et al, 2006). Samples were resolved on 12% sodium dodecyl sulfate polyacrylamide gel and immunoblotted with corresponding antibodies.…”
Section: Localization Of Exbb and Exbd Proteins In Synechocystis 6803mentioning
confidence: 99%
“…PCC 7120 [13,24]. For example, earlier reports by Norling et al demonstrated the extensive optimisation required to profile and study thylakoid and membrane-bound proteins and their successful characterisation [20,25,26]. Other notable published studies include the early work on Nostoc sp.…”
Section: Early Gel Proteomics Applied To Cyanobacteriamentioning
confidence: 99%